2020
DOI: 10.1038/s41467-020-19967-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular events of acute, resolving or progressive COVID-19 in SARS-CoV-2 infected non-human primates

Abstract: Understanding SARS-CoV-2 associated immune pathology is crucial to develop pan-effective vaccines and treatments. Here we investigate the immune events from the acute state up to four weeks post SARS-CoV-2 infection, in non-human primates (NHP) with heterogeneous pulmonary pathology. We show a robust migration of CD16 expressing monocytes to the lungs occurring during the acute phase, and we describe two subsets of interstitial macrophages (HLA-DR+CD206−): a transitional CD11c+CD16+ cell population directly as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 61 publications
(94 reference statements)
18
113
0
Order By: Relevance
“…In particular, the levels of pro-inflammatory CD14+CD16+ monocytes were elevated in the lungs of 28 hospitalized COVID-19 patients relative to healthy controls [ 184 ], which was corroborated by a study that found increased CD14+CD16+ monocytes with high expression of IL-6 in the peripheral blood of 33 COVID-19 patients [ 182 ]. IL-6 production by CD16+ monocytes exacerbates hyperinflammation in severe COVID-19 and is associated with lung pathology [ 182 , 185 ]. An observational study of 34 COVID-19 patients by Zhang et al [ 184 ] found an unusual heterogeneous monocyte response with increased intracellular staining for pro-inflammatory IL-6 as well as anti-inflammatory IL-10.…”
Section: Consequences Of Endothelium Dysfunction In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the levels of pro-inflammatory CD14+CD16+ monocytes were elevated in the lungs of 28 hospitalized COVID-19 patients relative to healthy controls [ 184 ], which was corroborated by a study that found increased CD14+CD16+ monocytes with high expression of IL-6 in the peripheral blood of 33 COVID-19 patients [ 182 ]. IL-6 production by CD16+ monocytes exacerbates hyperinflammation in severe COVID-19 and is associated with lung pathology [ 182 , 185 ]. An observational study of 34 COVID-19 patients by Zhang et al [ 184 ] found an unusual heterogeneous monocyte response with increased intracellular staining for pro-inflammatory IL-6 as well as anti-inflammatory IL-10.…”
Section: Consequences Of Endothelium Dysfunction In Covid-19mentioning
confidence: 99%
“…An observational study of 34 COVID-19 patients by Zhang et al [ 184 ] found an unusual heterogeneous monocyte response with increased intracellular staining for pro-inflammatory IL-6 as well as anti-inflammatory IL-10. Simultaneous elevation of cytokines involved in type 1 (IL-6) and type 2 (IL-10) immune responses may reflect a multiphasic monocyte/macrophage response against SARS-CoV-2 infection [ 185 ]. By examining temporal and spatial characteristics of monocytes in African green monkey and rhesus macaque animal models with COVID-19, Fahlberg et al [ 185 ] characterized an initial acute hyperinflammatory state with increased frequency of CD16+ monocytes in the lungs, followed by a gradual switch to a type 2 response, and corresponding increase in either anti-inflammatory IL-10 associated with disease resolution, or IL-6, which is associated with increased disease severity [ 185 ].…”
Section: Consequences Of Endothelium Dysfunction In Covid-19mentioning
confidence: 99%
“…TRAIL has previously been correlated with viral load during SARS-CoV-2 infection 10 , but we found it to be significantly decreased in the serum of RSV and SARS-CoV-2 patients compared to healthy donors in our cohort (Figure 5B). Additionally, CCL17 and CCL22, chemokines known to be involved in the mobilization of immune cell to the lungs 45,46 and reported to be increased in SARS-CoV-2 infection 10,47,48 , were decreased or unchanged in the serum compared to healthy donors in our cohort. These findings are most likely due to the timing of the sample collection from symptom onset; studies have shown that trafficking of immune cells by these chemokines are most elevated as early as 1 week after infection 47 , and since all of our samples came from hospitalized patients, some were collected weeks after symptom onset (Table 1).…”
Section: Pro-inflammatory Cytokines and Chemokines Are Increased Durimentioning
confidence: 56%
“…However, multi-lineage, morphological changes in circulating blood cells have been documented in patients with COVID-19 [3]. In addition, a recent study by Fahlberg et al [4] highlighted that infiltration of the lungs by monocytes and neutrophils is a significant contributor to severe COVID-19 pathology, and that pulmonary accumulations could persist for up to four-weeks post-infection. Fahlberg et al [4] postulate that enduring myelomonocytic infiltrates may partly explain the slow recovery from COVID-19 seen in humans.…”
Section: To the Editormentioning
confidence: 99%
“…In addition, a recent study by Fahlberg et al [4] highlighted that infiltration of the lungs by monocytes and neutrophils is a significant contributor to severe COVID-19 pathology, and that pulmonary accumulations could persist for up to four-weeks post-infection. Fahlberg et al [4] postulate that enduring myelomonocytic infiltrates may partly explain the slow recovery from COVID-19 seen in humans. This raises the question as to whether changes in monocyte or neutrophil populations precede severe pathophysiological outcomes which could enable clinicians to target patients at risk of clinical deterioration.…”
Section: To the Editormentioning
confidence: 99%